The Application of Qur'anic Values of Tolerance and Harmony in the Social Life of Muslim Communities - Hidayah, Sabilatul; Zayyadi, Ach. (STAI Publisistik Thawalib Jakarta, 2024)
The lack of religious education and tolerance in Sumber Logan village intensifies social tensions arising from differing interpretations of Qur'anic values. This study aims to identify and analyze the application of tolerance and harmony values in the Qur'an, as well as provide recommendations for improving social harmony in the community. This research uses a phenomenological qualitative approach with interviews, observations, and documentation. Data were analyzed through condensation, presentation, and verification. Data validity is ensured through credibility, dependability, and confirmability. The research findings indicate: (1) The values of tolerance and harmony in the Qur'an are reflected in Surah An-Nahl 125 and Ali 'Imran 64. (2) Parents, religious leaders, village officials, and teachers play a role in instilling values of tolerance and harmony through character education, religious understanding, and promoting respect for differences, avoiding violence, and honoring freedom of belief. (3) Recommendations include promoting tolerance through digital da'wah, interactive learning, discussion forums, role model initiatives, peace-building programs, fostering respect for diversity, anti-violence counseling, and engaging in religious activities. In conclusion, the local community integrates religious values into daily life to deepen faith and devotion to Allah SWT.